Effect of Growth Media Based on Palm Oil Fiber Waste on the Growth of Sea Pandan (Pandanus tectorius parkinson Ex Z) - Apriyanto, Enggar; Sinurat, Berliana (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Fruit fiber oil palm which be generated by the oil palm industries has a potential resource for a growth media. This study aims is to evaluate the effect of planting media based on the fruit oil palm fiber waste on the growth of sea pandan seedlings. This research was conducted in August - October 2020 at the Nursery and Laboratory of the Forestry Department, Faculty of Agriculture, Bengkulu University. The experimental design used in this study was a single factor CRD (completely randomized design), 5 treatments and 3 replications with 6 seedling each replication. The five treatmens was 1) 100% Palm Oil Fruit Fiber, 2) 100% Cow Manure, 3) combination of Palm Fruit Fiber Waste ((75%) and Cow Manure (25%), 4) Palm Oil Fruit Fiber Waste (50%) and Caw Manure (50%) and 5) Combination of Palm Fruit Fiber Waste (25%) + Cow Manure (75%). The results indicated that the different combination media resulted in the different of Pandanus laut growth. The combination media of Palm Oil Fruit Fiber Waste (75%) + Cow Manure (25%) gave the best growth of sea pandanus.